GEO-NEUTRINOS: A NEW PROBE OF EARTH'S INTERIOR - Fiorentini G.; Mantovani F.; Lissia M.; Vannucci R. (My University, 2005)
In preparation to the experimental results which will be available in the future, we study geo-neutrino production for different models of mantle convection and composition. By using global mass balance for the Bulk Silicate Earth, the predicted flux contribution from distant sources in the crust and in the mantle is fixed within a total uncertainty of ±15%. We also discuss regional effects, provided by subducting slabs or plumes near the detector. In 4 years a 5-kton detector operating at a site relatively far from nuclear power plants can achieve measurements of the geo-neutrino signal accurate to within ±5%. It will provide a crucial test of the Bulk Silicate Earth and a direct estimate of the radiogenic contribution to terrestrial heat. © 2005 Elsevier B.V. All rights reserved.
Keywords: BULK SILICATE EARTH; MANTLE CIRCULATION; NEUTRINOS; TERRESTRIAL HEAT FLOW; URANIUM AND THORIUM ABUNDANCES